Pengaruh Tingkat Pengetahuan Kewirausahaan terhadap Minat Berwirausaha - Megantara, Bilqis Damai Nuraini; Maulida, Hilma; Najmi, Nur Ainun (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Abstract. There is still unemployment in Indonesia due to the high number of workers than available job opportunities, causing a large labor force but very few job opportunities. Therefore, the need for knowledge and skills in the field of entrepreneurship to encourage a person's interest in entrepreneurship. In line with this, the purpose of this study is to determine how influential the level of entrepreneurial knowledge is on the entrepreneurial interest of members of the Siliwangi University Student Cooperative Student Activity Unit (UKM Kopma Unsil). The data collection technique in this study used a Likert scale questionnaire as a data collection instrument. The type of research used is to use quantitative methods, while for data analysis techniques using simple linear regression. The results of this study indicate that the level of entrepreneurial knowledge can have a positive effect on entrepreneurial interest of members of UKM Kopma Unsil, which means that the higher the level of entrepreneurial knowledge of members of UKM Kopma Unsil, the higher the level of entrepreneurial interest.